(untitled) (Revista de Artes Marciales Asiáticas, 2021)
Editors • Emerson Franchini – University of São Paulo, São Paulo (Brazil) • Tomás Herrera-Valenzuela – Universidad de Santiago de Chile (Chile) Authors • Ursula Ferreira Julio – University of São Paulo, São Paulo (Brazil) • Emerson Franchini – University of São Paulo, São Paulo (Brazil) • Tomás Herrera-Valenzuela – Universidad de Santiago de Chile (Chile) • João Paulo Lopes-Silva – CESMAC University Centre (Brazil) • Braulio Henrique Magnani Branco – Cesumar University (Brazil) • Jonatas Ferreira da Silva Santos – Federal University of the Jequitinhonha and Mucuri Valleys (Brazil) • Rubens Santos-Junior – State University of Pará (Brazil) Reviewers • Filipa Almeida – Universidad de Granada (Spain) • Juan Bonitch Góngora – Universidad de Granada (Spain) • Eduardo Carballeira Fernández – Universidade da Coruña (Spain) • Daniele Detanico – Universidade Federal de Santa Catarina (Brazil) • Raquel Escobar Molina – Universidad de Granada (Spain) • Matheus Hausen – Brazil Olympic Committee (Brazil) • Raquel Hernandez García – Universidad de Murcia (Spain) • Eliseo Iglesias Soler – Universidade da Coruña (Spain) • Carlos Montero Carretero – Universidad Miguel Hernández (Spain) • Emanuela Pierantozzi – Università degli Studi di Genova (Italy) • Luis Santos Rodríguez – Universidad de León (Spain) • Jozef Simenko – University of Essex (UK)